INSIDIATOREM INTERFICI IURE POSSE KONTRATYPY JAKO SPOSÓB OBRONY W PROCESIE – PRO MILONE CYCERONA - Loska, Elżbieta (Zeszyty Prawnicze, 2017)
Insidiatorem interfici iure posse. Legitimate Defence as the Method of Legal Argumentation – pro Milone Summary In the trial of Titus Annius Milo, charged for a murder, the strategy of defence was constructed upon the fact that the defendant had acted in self-defence. According to Cicero the circumstances which could be perceived as justified were those in which one undertook a forcible course of action against the violence. The orator explains that the common sense gives all the people a possibility of defence against any unjustified act of aggression. Each human being is supposed to know this rule from the very beginning of his life. Therefore in a situation of a life danger caused by an enemy or an villain, every action taken to eliminate it finds a full moral justification.